Effect of DC Voltage Source and Motor Speed Ratio for Energy Saving Electric Vehicles - Saksri Kaensom2Natthawath Woranetsuttikul, (Design Engineering, 2021)
This article is a study of the effect of DC voltage source and motor speed ratio of energy-saving electric vehicle. The voltage levels are divided into 3 levels: 24 Vdc, 36 Vdc and 48 Vdc, and have different ratios according to the increased motor speed. The motor used in the experiment was two 200 W brushless DC electric motors with 12-pole low-speed motor and 4-pole high-speed motor. The experiment was conducted by setting all conditions to the same values except for the change in voltage and ratio. Test running at a distance of 10 km in no more than 25 minutes or an average speed of 25 km/hr. with the vehicle weighs 32 kg, and the driver weighs 50 kg. The results of the test showed that when the battery voltage is higher, the power loss is less and the motor rpm increases, resulting in higher motor speed ratio and torque. Therefore, the energy efficiency rate is higher according to the voltage level. The low-speed motor gives the best test results at 48 Vdc voltage, 1 to 4 ratio, energy efficiency 364.96. km/kWh, and the vehicle can run up to 364.96 km.